Sisters in Arms - Levi, Avital Livneh (Go2Films, 2006)
Verzio FF Submission The story of five Israeli women who, in their youth, chose to leave the comfortable city life to pursue the ideological struggle of the settler movement. They became close friends and for more than 14 years, they firmly kept a yearly ritual of taking a holiday together - a vacation just for them, far from the settlement, their husbands, their work obligations and their children. In 2004 a terrorist murdered one of them, shattering the group. The film brings the four women back together on their traditional vacation where they look back at their shared memories contemplating on youth, ideals and later realities.